Integrating local wisdom into ipas learning to strengthen students’ critical thinking: An analysis of gondolio as a learning resource in elementary schools - Aris Naeni Dwiyanti (CV. FOUNDAE, 2026)
Background: Critical thinking is widely recognized as an essential competence in twenty-first century education. Integrating local wisdom into IPAS learning can connect scientific concepts with students’ cultural and environmental contexts. Aims: This study aims to examine how local wisdom-based learning contributes to the development of critical thinking in IPAS learning and to analyze the potential of Gondolio, a traditional bamboo musical instrument from Banyumas, as a learning resource in elementary schools. Method: This research employed a mixed-method approach combining a systematic literature review and qualitative analysis. The literature review examined studies related to local wisdom and critical thinking in science learning published between 2019 and 2024 using Publish or Perish and VOSviewer. Qualitative data were obtained through interviews with local cultural practitioners and analysis of curriculum documents from the Merdeka Curriculum. Results: The literature review indicates that integrating local wisdom into science-related learning can support the development of students’ critical thinking through contextual learning experiences. The qualitative findings show that Gondolio contains several concepts relevant to IPAS learning, including sound phenomena, plant classification, material changes, and cultural diversity. Conclusion: Using Gondolio as a learning resource provides contextual learning opportunities that connect scientific concepts with local cultural practices, thereby supporting the development of students’ critical thinking in elementary education.